Property Rights of Nigerian Women at Divorce: A Case for a Redistribution Order - Chinedu Justin Efe; Oghenerioborue Esther Eberechi (Potchefstroom Electronic Law Journal, 2020)
In Nigeria, marriage is hardly conceived as a partnership of equals in relation to the property rights of spouses during marriage and at divorce. This is because the Nigerian courts do not redistribute property at divorce. This leaves the financially weaker spouse (usually the wife) at an economically disadvantaged position. This article therefore compares the position of the matrimonial laws in England with that of Nigeria, whether there are provisions for the redistribution of property between the spouses at divorce. The comparative analysis reveals that family laws in England empower the family court to redistribute property amongst spouses at divorce. On the contrary, the matrimonial property laws in Nigeria provide for the settlement of property at divorce. The analysis also reveals that the courts in Nigeria adopt the strict property rights approach in ordering the settlement of property, which is detrimental to the wife. The article also makes a case for a redistribution through the economic analysis of the worth of a housewife. The authors therefore argue that the Nigerian courts should depart from this approach and borrow from the English courts. The authors recommend the amendment of the matrimonial property laws to fill this gap. That would enable the Nigerian courts to make a redistribution order, so as to vary the recognised property rights of spouses in order to provide compensation for any reasonable loss caused by marriage and ensure that the financial benefits of marriage are shared on a just and equitable basis.